Proclaiming the parables: preaching and teaching the kingdom of God - Long, Thomas G. (Westminster John Knox Press, 2024)
Intro -- Praise Page -- Half Title -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Preface -- 1. Jesus' Parables on the Playground of the Scholars -- 2. Decisions Preachers Make -- 3. Mark's Parables: Background -- 4. Mark: The Parables -- The Parable of the Sower (Mark 4:1-20) -- The Parable of the Seed Growing Secretly (Mark 4:26-29) -- The Parable of the Mustard Seed (Mark 4:30-32) -- The Parable of the Wicked Tenants (Mark 12:1-12) -- The Parable of the Doorkeeper (Mark 13:32-37) -- 5. Matthew's Parables: Background -- 6. Matthew: The Parables -- The Parable of the Sower (Matthew 13:1-23) -- The Parable of the Wheat and the Weeds (Matthew 13:24-30, 36-43) -- The Parable of the Mustard Seed (Matthew 13:31-32) -- The Parable of the Woman and the Yeast (Matthew 13:33) -- The Parable of the Treasure Hidden in a Field (Matthew 13:44) -- The Parable of the Pearl of Great Value (Matthew 13:45-46) -- The Parable of the Net (Matthew 13:47-50) -- The Parable of the Sheep Gone Astray (Matthew 18:10-14) -- The Parable of the Unforgiving Slave (Matthew 18:23-35) -- The Parable of the Laborers in the Vineyard (Matthew 20:1-16) -- The Parable of the Two Sons (Matthew 21:28-32) -- The Parable of the Wicked Tenants (Matthew 21:33-46) -- The Parable of the Wedding Banquet (Matthew 22:1-14) -- The Parable of the Ten Bridesmaids (Matthew 25:1-13) -- The Parable of the Talents (Matthew 25:14-30) -- The Parable of the Sheep and the Goats (Matthew 25:31-46) -- 7. Luke's Parables: Background -- 8. Luke: The Parables -- The Parable of the Sower (Luke 8:4-15) -- The Parable of the Good Samaritan (Luke 10:25-37) -- The Parable of the Friend at Midnight (Luke 11:5-8) -- The Parable of the Rich Fool (Luke 12:13-22) -- The Parable of the Barren Fig Tree (Luke 13:6-9).